E-Voting Management System for Beginners Voters - Berlina Wulandari; Fitrah Satrya Fajar Kusumah; Nadia Amanda Febrianti (Universitas Ibn Khaldun Bogor, 2025)
Elections at the beginner voter level are still mostly done manually. This manual method is considered lacking in efficiency and is still considered conventional because it does not take advantage of technological advances. Based on this statement, several discussions emerged regarding the process of modernizing voting, namely the election process using e-voting. The e-voting system provides convenience for both voters and the executive committee. The implementation of the election by e-voting requires a system to regulate matters relating to the implementation of the election because in its implementation each agency that uses e-voting has different election data. Therefore, this study makes an e-voting management system for novice voters. This e-voting management system can manage election data such as agency profiles, election schedules, and candidates, up to the Permanent Voters List (DPT). The data used in this study were obtained from agencies that use e-voting. The method used is the waterfall model which consists of system analysis, system design, coding, and testing. Based on the test results, this system is running well according to its function. The e-voting management system makes it easier for the organizers and the implementing committee, before the election and in the post-election process.